AB1187 Autoantibodies recognizing carbamylated proteins (anti-carp) in sera of patients with JIA. (23rd January 2014) - Hissink Muller, P.C.; Anink, J.; Shi, J.; Levarht, N.; Reinards, T.H.; Otten, M.H.; van Tol, M.J.; Jol-van der Zijde, C.; Allaart, C.F.; Hoppenreijs, E.P.; Koopman-Keemink, Y.; Dolman, K.; et al.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) have a low prevalence in Juvenile Idiopathic Arthritis (JIA). Autoantibodies recognizing carbamylated protein (anti-CarP) are a promising new serological marker for ACPA negative Rheumatoid Arthritis and are associated with a more severe clinical course (Shi et al, 2011). Objectives: To determine the presence of anti-CarP antibodies in sera of JIA patients and to investigate their prognostic value. Methods: Samples of 249 patients with all subgroups of JIA, taken at different time points in their disease course and 107 healthy partially age matched controls were analyzed for the presence of anti-CarP antibodies as well as ACPA (commercial CCP2 ELISA). Cut-off for positivity was determined in the sera of the healthy controls as the mean plus two times standard deviation. Results: The serum samples came from patients with all different subtypes of JIA (median age 12, 1 years, IQR 8, 1-15, 7 median disease duration 2, 2 years IQR 0, 7-6, 4) including 19 polyarticular rheumatoid factor positive patients. IgG antibodies recognizing carbamylated antigens were present in sera of 12, 9% (32/249) of all JIA patients vs 2, 8% (3/107) in the controls (p=0, 002). Anti-CarP antibodies were detected in 58% (11/19) of the rheumatoid factor positive polyarticular JIA patients (p<0, 001) vs 10% (9/90) in the rheumatoid factor negative polyarticular JIA patients. Conclusions: Anti-CarP antibodies can be detected in sera of patients with JIA, mainly in the rheumatoid factor positive polyarticular subgroup, which is the JIA subtype that shows the most resemblance with RA in adults. Correlations between anti-CarP antibodies and disease characteristics are currently under investigation. References: Shi J et al. Autoantibodies recognizing carbamylated protein are present in sera of patients with rheumatoid arthritis and predict joint damage. PNAS, October 2011;108(42):17372-7 Disclosure of Interest: P. Hissink Muller Grant/Research support from: Pfizer and the Dutch League against Rheumatism, J. Anink: None Declared, J. Shi: None Declared, N. Levarht: None Declared, T. Reinards: None Declared, M. Otten: None Declared, M. van Tol: None Declared, C. Jol-van der Zijde: None Declared, C. Allaart: None Declared, E. Hoppenreijs: None Declared, Y. Koopman-Keemink: None Declared, K. Dolman: None Declared, J. van den Berg: None Declared, M. van Rossum: None Declared, L. van Suijlekom-Smit: None Declared, M. Schilham: None Declared, R. ten Cate: None Declared, R. Toes: None Declared, L. Trouw: None Declared